Analysis of heavy metals and aromatics compounds in soil layers of a sanitary landfill - Forti, Juliane C. [UNESP]; Lima, Paula G. [UNESP]; Reis, André R. [UNESP]; dos Santos, Felipe A. [UNESP]; Braga, Sérgio S. [UNESP] (Wiley, 2019)
Solid waste presents the potential for contamination of the soil when it is improperly managed. One of the great challenges of today's society is to promote the proper disposal of municipal solid waste in order to guarantee the safety of public health and to avoid risks to the environment. In this context, the objective of this study is to analyze the concentration profiles of heavy metals and aromatic hydrocarbons of risk that human health in landfill soil. Such works provides an important tool to evaluate the possible presence of contaminants from inappropriate waste disposal, as well as to assist in the management of waste and to prevent environmental contamination. In order to analyze cadmium (Cd), lead (Pb), nickel (Ni), arsenic (As), and mercury (Hg), which are toxic elements, and aromatic hydrocarbons, including benzene, toluene, ethylbenzene, o-xylene, m-xylene, and p-xylene, soil samples were collected at different sites and depths. Neither Cd nor As was detected in any of the samples that were analyzed. Pb levels ranged from 5.34 milligrams per kilograms (mg/kg) to 7.40 mg/kg, Ni levels ranged from 2.17 mg/kg to 3.00 mg/kg, and Hg levels ranged from 75.4 micrograms per kilograms (μg/kg) to 88.3 μg/kg. The aromatic hydrocarbon compounds of benzene, toluene, ethylbenzene, and o-xylene were below 5.5 μg/kg, and m-, p-xylene was below 11 μg/kg. The analysis of heavy metals and aromatic hydrocarbons present in the landfill soil showed concentrations below the soil quality guideline values of the Brazilian National Environment Council (CONAMA) Resolution 420, which has criteria for the presence of chemical substances in soil for Brazil. Therefore, the low levels of chemicals may be related to the operational time of the landfill or to the population profile of the municipality, which is predominantly composed of persons involved in family-based agriculture.
Keywords: aromatic compounds; environmental pollution; heavy metals; sanitary landfill; soil pollution; solid waste